Usefulness of high‐risk HPV early oncoprotein (E6 and E7) serological markers in the detection of cervical cancer: A systematic review and meta‐analysis. Issue 1 (9th June 2022) - Singini, Mwiza Gideon; Singh, Elvira; Bradshaw, Debbie; Ramaliba, Thendo; Chen, Wenlong Carl; Motlhale, Melitah; Kamiza, Abram Bunya; Babb de Villiers, Chantal; Muchengeti, Mazvita; Mathew, Christopher G.; Newton, Robert; Bender, Noemi; et al.
Abstract: We reviewed the literature on the importance of selected anti‐high‐risk human papillomavirus (HR‐HPV) antibodies (namely, 16/18 and early oncoproteins E6 and E7) as potential serological markers for early detection of individuals at high risk of cervical cancer. We searched for studies in PubMed and Embase databases published from 2010 to 2020 on antibodies against HR‐HPV E6 and E7 early proteins and cervical cancer. Pooled sensitivity and specificity for HPV16 and HPV18 antibodies were calculated using a bivariate hierarchical random‐effects model. A total of 69 articles were identified; we included three studies with 1550 participants. For the three HPV16/18 E6 and E7 antibody tests, enzyme‐linked immunosorbent assay‐based assays had a sensitivity of 18% for detecting CIN2+ (95% confidence interval [CI]: 15–21) and a specificity of 96% (95% CI: 92–98), for slot‐blot, sensitivity was 28.9% (95% CI: 23.3–35.1) and specificity was 72% (95% CI: 66.6–77.0) for detecting CIN2+, and for multiplex HPV serology assay based on a glutathione S ‐transferase, sensitivity was 16% (95% CI: 8.45–28.6) and specificity was 98% (95% CI: 97–99) for detecting invasive cervical cancer. HR‐HPV16/18 E6 and E7 serological markers showed high specificity, but sensitivity was suboptimal for the detection of cervical cancer in either population screening settings or as point‐of‐care screening tests.